The effect of number and position of braced frames on column behavior of the dual steel structural system (MRF and EBF) (With a view on amplified seismic load) - Mohammadi, Sajjad; Moghaddam, Abd-ol-Reza Sarvghad; Faroughi, Alireza (Ciência e Natura, 2015)
In seismic design of structures, determination of number and position of braced frames, considering the architectural scheme of projects, is usually confronted by obstacles. Due to this fact, in some cases, selecting the best location and number of braced bays has led to mistakes in determination of their adjacent members (columns) design loads. One of the seismic design requirements of lateral resisting system is to control the columns adjacent to braced bays for load combinations of amplified seismic load, which is a function of over-strength factor of the structure. This research aims to present and introduce the best structural model of number and position of braced frames in a structural system, such as steel moment resisting frame and eccentric braces dual system; because in 3rd revision of Iranian 2800 standard of seismic provision, there are statements and criteria provided only for capacity of moment frame, not for braces. Though the amplified seismic load function is controlled in models which columns are connected to braces in 2 directions, and seismic loads are applied in those 2 directions, number of damage hinges (Exceeding CP) is significantly increased in comparison to the models with straggly braces. As the increase in axial force of these columns leads to decrease in their moment capacity (despite controlling the amplified seismic load provision), columns in dual systems that resist flexure, would be damaged and exceed the collapse threshold much sooner than other columns. This important fact is not presented in Iranian or even American codes and provisions.